Biology: A Global Approach - Neil A. Campbell (Pearson Education, 2018)
The 11th Edition of the best-selling Biology: A Global Approach, Global Edition, sets students on the path to success in biology through its clear and engaging narrative, superior skills instruction, innovative use of art and photos, and fully integrated media resources to enhance teaching and learning. To engage learners in developing a deeper understanding of biology, the 11th Edition challenges them to apply their knowledge and skills to a variety of new hands-on activities and exercises in the text and online. Content updates throughout the text reflect rapidly evolving research, and new learning tools include Problem-Solving Exercises, Visualizing Figures, Visual Skills Questions, and more. MasteringBiology (TM) is not included. Students, if MasteringBiology is a recommended/mandatory component of the course, please ask your instructor for the correct ISBN. MasteringBiology should only be purchased when required by an instructor. Instructors, contact your Pearson representative for more information. MasteringBiology is an online homework, tutorial, and assessment program designed to work with this text to engage students and improve results. Interactive, self-paced tutorials provide individualized coaching to help students stay on track. With a wide range of activities available, students can actively learn, understand, and retain even the most difficult concepts.